2011
DOI: 10.1111/j.2044-8325.2011.02032.x
|View full text |Cite
|
Sign up to set email alerts
|

The deviant citizen: Measuring potential positive relations between counterproductive work behaviour and organizational citizenship behaviour

Abstract: Studies have shown a strong negative correlation between counterproductive work behaviour (CWB) and organizational citizenship behaviour (OCB), and opposite correlations with hypothesized antecedents. Such observed correlations may have been erroneously caused by three measurement artefacts: items measuring absence of CWBs, rather than behaviours that exceed requirements or expectations in OCB scales; supervisory halo; and agreement rather than frequency response format. A new OCB scale, the OCB-checklist (OCB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
168
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 208 publications
(185 citation statements)
references
References 55 publications
(99 reference statements)
7
168
2
1
Order By: Relevance
“…The first reason is due to the fact that positive job attitudes promotes various extra-role behaviors (Bateman & Organ, 1983;Ilies, Scott, & Judge, 2006;Van Dyne, Graham, & Dienesch, 1994) that are an essential part of transformational leadership (Bass, 1985(Bass, , 1990(Bass, , 1997. Two examples of recently-developed organizational citizenship behaviors (OCBs) that have been empirically linked to more positive job attitudes are: (1) "[lending] a compassionate ear when someone had a work problem," and (2) "[taking] time to advise, coach, or mentor a co-worker" (Fox, Spector, Goh, Bruursema, & Kessler, 2012); both of these OCBs illustrate, also, what has been called the individualized consideration dimension of transformational leadership. A number of studies suggest that job attitudes are important determinants of various voluntary behaviors such as OCBs (e.g.…”
Section: Positive Job Attitudes Foster Transformational Leadershipmentioning
confidence: 98%
“…The first reason is due to the fact that positive job attitudes promotes various extra-role behaviors (Bateman & Organ, 1983;Ilies, Scott, & Judge, 2006;Van Dyne, Graham, & Dienesch, 1994) that are an essential part of transformational leadership (Bass, 1985(Bass, , 1990(Bass, , 1997. Two examples of recently-developed organizational citizenship behaviors (OCBs) that have been empirically linked to more positive job attitudes are: (1) "[lending] a compassionate ear when someone had a work problem," and (2) "[taking] time to advise, coach, or mentor a co-worker" (Fox, Spector, Goh, Bruursema, & Kessler, 2012); both of these OCBs illustrate, also, what has been called the individualized consideration dimension of transformational leadership. A number of studies suggest that job attitudes are important determinants of various voluntary behaviors such as OCBs (e.g.…”
Section: Positive Job Attitudes Foster Transformational Leadershipmentioning
confidence: 98%
“…We chose to examine organizational behaviors because the workplace affords employees with myriad opportunities to act ethically and unethically, and most adults spend a substantial portion of their lives at work. Examples of OCB include taking time to advise, coach, or mentor coworkers; lending a compassionate ear when someone has a work problem; and changing vacation schedules, work days, or shifts to accommodate coworkers' needs (Fox, Spector, Goh, Bruursema, & Kessler, 2012). Examples of CWB include being nasty or rude to clients or customers; taking supplies or tools home without permission; and leaving work earlier than one is allowed (Spector et al, 2006).…”
Section: Defining Morality and Ethicsmentioning
confidence: 99%
“…Vigoda-Gadot (2006) suggested that OCB (e.g., altruistic behavior, conscientiousness, sportsmanship, and courtesy) will lose its voluntary meaning when the external pressure is applied. Vigoda-Gadot (2006, 2007 further descripted this phenomenon as compulsory citizenship behavior (CCB; employees' engagement in extra-role activities which often against their will), reflecting a different dynamic than voluntary beneficence (Fox, Spector, Goh, Bruursema, & Kessler, 2012).…”
mentioning
confidence: 99%